1999
DOI: 10.1076/ejom.37.2.126.4748
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of GABA-immunolabeling in the Early Zebrafish (Danio rerio) Brain

Abstract: The spatial and temporal pattern of GABA-expression in the brains of zebrafish (Danio rerio) embryos was studied by means of immunohistochemical techniques. GABA is said to exert neurotrophic actions in the early regulation of the differentiation of the central nervous system. In early stages GABAergic cells form distinct clusters throughout the CNS. As development progresses, more GABAergic clusters appear, and a pattern of GABAergic axonal projections is well defined. Although there is a corresponding patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Studies in the early zebra fish (Danio rerio) demonstrated that GABA was distributed in discrete brain regions during development [Doldan et al, 1999]. Another study also described the developmentally dependent appearance of GABA-ir neurons in the early brain of the teleost, Gasterosteus aculeatus L.; GABA appeared to be expressed in the first differentiated neuronal populations of the teleost brain [Ekström and Ohlin, 1995].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Studies in the early zebra fish (Danio rerio) demonstrated that GABA was distributed in discrete brain regions during development [Doldan et al, 1999]. Another study also described the developmentally dependent appearance of GABA-ir neurons in the early brain of the teleost, Gasterosteus aculeatus L.; GABA appeared to be expressed in the first differentiated neuronal populations of the teleost brain [Ekström and Ohlin, 1995].…”
Section: Discussionmentioning
confidence: 89%
“…In rats, a population of GABAergic neurons was found in the diencephalon, including the hypothalamus, early in development [Lauder et al, 1986;Tobet et al, 1997]. In teleosts, GABA neurons emerge early in development within the rostral prosencephalon [Ekström and Ohlin, 1995;Doldan et al, 1999]. In Amphioxus, GABA-ir cells were localized caudal to the infun-Reed/MacIntyre/Tobet/Trudeau/ MacEachern/Rubin/Sower dibular organ, which is thought to correspond to the GABA-ir fibers observed in the ventral hindbrain of Xenopus embryos [Roberts et al, 1987;].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we do not know the ultimate fate of the neurons that we have identified in this study. Several neurotransmitters have been identified in the hypothalamus in zebrafish larvae and adults (Doldan et al, 1999;Poon et al, 2003;Ross et al, 1992;Teraoka et al, 2004). In addition, dopaminergic neurons project from the tuberal hypothalamus to the subpallium in adults, but it remains unclear when the projection arises (Rink and Wullimann, 2001).…”
Section: Evolutionary Conservation Of Sox3 and Wnt Function In Postermentioning
confidence: 99%
“…The embryonic cell clusters contain the first transmitter phenotypic cells, and the vrc and vcc in zebrafish comprise subpopulations of cell clusters holding different primary transmitter differentiated cells, i.e. catecholaminergic, serotonergic and gamma amino butyric acid expressing (GABA) cells (Doldan et al, 1999;Ellingsen et al, 1998;Holzschuh et al, 2001). GABAergic cells are part of all embryonic cell clusters from an early stage, whereas nNOS and the primary catecholaminergic and serotoninergic cells are initially restricted to the vrc and vcc.…”
Section: Ontogeny Of Nnos and Temporal Correlations With Cgmpmentioning
confidence: 99%